China Economic Update, June 2015 - Smits, Karlis (World Bank, Washington, DC, 2015)
Chinas economic growth continues to moderate, in 2014 gross domestic product (GDP) expanded by 7.4 percent, within the governments indicative growth target of about 7.5 percent for the year, but sharply slower than the 10 percent annual growth rate china averaged for three consecutive decades. An orderly correction in real estate - reflecting policy efforts to reduce supply mismatches and tighten nonbank credit - continues to weigh on economic activity. Ongoing adjustments in real estate, a buildup of excess capacity, and decelerating export growth are affecting industrial activity. In contrast growth in services remained robust as composition of growth continues to improve.